HUBUNGAN PERILAKU KELUARGA SADAR GIZI DENGAN KEJADIAN STUNTING BALITA DAN EVALUASI PROGRAM - Agustina, Ria; Utami, Tri Niswati; Asriwati, Asriwati (Universitas Prima Indonesia, 2020)
The results of monitoring the nutritional status of children under five years (toddler) at the Puskesmas Sigambal Rantau Selatan Sub-District, Labuhanbatu District short prevalence is still high at 15.31% and very short 10.15% in 2017. The study aims to analyze the relationship of nutrition conscious family behavior with incidence of toddler stunting and nutrition awareness family program evaluation. The population was mothers with children aged 12-59 months, 119 people and a sample of 92 people. The sampling technique is a random table technique. Data were analyzed univariate, bivariate and multivariate using multiple logistic regression tests. Qualitative data are data reduction, presentation and conclusion drawing. The results showed that the consumption of various foods (0,000) was related to the incidence of toddler stunting and as a dominant factor. Weighing variables, iodized salt consumption, exclusive breastfeeding and nutritional supplements (vitamin A) are not related. The interview found that the evaluation of the nutrition awareness family program was not yet supported by the availability of health workers, cadre assistants, funds and infrastructure, as well as cross-sectoral implementation. Program indicators were not reached because they did not specialize in the nutrition awareness family program. It is recommended that the Public Health Office establish a special program for Nutrition Awareness Families, increase cross-sector collaboration and add cadre assistants to promote the importance of nutrition for the community.